Compartmented microfluidic bioreactor system using magnetic enzyme immobilisates for fast small‐scale biotransformation studies. Issue 7 (17th April 2015) - Hübner, Jonas; Brakowski, Regina; Wohlgemuth, Jonas; Brenner‐Weiß, Gerald; Franzreb, Matthias
<x xml:space="preserve">Abstract</x> In the last decade, microfluidic bioreactor systems became increasingly important due to their high suitability for lab‐on‐a‐chip applications and resource‐saving experiments with small sample volumes. Here, a prototype of a microfluidic device for fast small‐scale investigations of enzymatic and biochemical reactions is introduced. Single or consecutive enzyme‐catalyzed reactions can be implemented within compartmented reaction environments separated by immiscible fluidic plugs. By immobilizing one of the reactants onto magnetic microcarriers, a fast and easy separation of the reaction products is possible allowing the realization of a sequence of different reaction steps with different enzymes and varying chemical environments. Besides permanent magnetic fields for separation processes, alternating electromagnetic fields can be applied to resuspend the carriers. This leads to an intense mixing as well as even microcarrier distribution within the compartment. In a proof of concept, kinetic studies of HRP immobilized onto polyvinyl alcohol‐magnetite composite microcarriers are presented. The results showed a specific enzyme activity of approximately 89 units per gram immobilized biocatalyst under the applied reaction conditions. In addition, results of recycling experiments point out the importance of the magnetically induced resuspension. While ten times reuse with immobilisate resuspension resulted in substrate conversion yields between 95 and 65%, the same experiment without the magnetically induced resuspension showed conversion yields below 10% over all cycles.